Reflections on dismissals in Peru in the Bicentenary - Jaimes Reátegui, Susan (2022)
The title of this article responds to my experience as a judge of the Labor Court in and for Huanuco. Based on the notes of the closed cases on the different types of dismissals brought before my court, the data contained in statistical tables is analyzed to establish what type of contracts originated the termination of employment of the affected employees. The referred data shows that the claims were settled according to the law, the case law and the doctrine established in Peru over the course of the years, and it is concluded that the employees were the most affected and the municipalities were the most sued. Finally, proposals are made to prevent unjustified and/or arbitrary dismissals, and the scope of the binding precedent of the Huatuco case is explained.